2021
DOI: 10.3390/ijerph18084029
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Delirium during ECMO Therapy in a Critical Care Unit in Poland—A Cross-Sectional Pilot Study

Abstract: Background: The problem of delirium during extracorporeal membrane oxygenation (ECMO) therapy, which has rarely been studied, is an important issue since it is necessary to ensure patient safety during therapy. This study aimed to show the incidence of delirium in patients after extracorporeal membrane oxygenation therapy and factors affecting the occurrence of delirium in this group of patients. Design: A cross-sectional study was conducted. Method: The study involved a group of patients from an intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
2
2
2
Order By: Relevance
“…24 Therefore, the method of screening and measuring delirium among ECMO patients in their study is different from our study, and careful interpretation is needed to understand our current findings and the results of Krupa et al's study. 24 In this study, we observed that older age, male sex, longer duration of ICU stay, and underlying depression were associated with a higher incidence of delirium among South Korean ECMO survivors. This is in keeping with a report where older age and length of hospital and ICU stay were shown to be risk factors for the development of delirium among critically ill patients, 25 and another where male sex and underlying depression were shown to be risk factors for the development of delirium among elderly and hospitalized patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…24 Therefore, the method of screening and measuring delirium among ECMO patients in their study is different from our study, and careful interpretation is needed to understand our current findings and the results of Krupa et al's study. 24 In this study, we observed that older age, male sex, longer duration of ICU stay, and underlying depression were associated with a higher incidence of delirium among South Korean ECMO survivors. This is in keeping with a report where older age and length of hospital and ICU stay were shown to be risk factors for the development of delirium among critically ill patients, 25 and another where male sex and underlying depression were shown to be risk factors for the development of delirium among elderly and hospitalized patients.…”
Section: Discussionsupporting
confidence: 90%
“…24 Therefore, the method of screening and measuring delirium among ECMO patients in their study is different from our study, and careful interpretation is needed to understand our current findings and the results of Krupa et al's study. 24…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Delirium, characterized by acute and uctuating alterations in consciousness, often precipitated by underlying medical illness 1 , is the most common neurological complication observed in intensive care units (ICUs), with a reported prevalence of up to 82% in mechanically ventilated patients 2 . Delirium prevalence has been studied in critically ill patients, including those with post-operative complications 3 , general ICU needs 2,4,5 , acute respiratory distress syndrome 6 (ARDS), extracorporeal membrane oxygenation (ECMO) 7 support, intracerebral hemorrhage 8 , status epilepticus 9 , and acute heart failure 10 . In many of these studies 2,4,8,10 , delirium portended worsened patient survival.…”
Section: Introductionmentioning
confidence: 99%